Mengupas Ragam Bentuk Penafsiran Al-Qur’an - Maryam R. Aisy; Indah Fatiha; Jihaddifa Jihaddifa; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Interpretation of the Qur'an is an effort to understand Allah's verses through various methods, including tafsir bil-ma'tsur, tafsir bil-ra'yi, and tafsir Isyari. Tafsir bil-ma'tsur relies on the Qur'an, hadith, and the understanding of the companions and the tabi'in, carrying strong authority but not without critique regarding the authenticity of its chains of narration and the potential inclusion of Israiliyat. Tafsir bil-ra'yi employs reason and logic, divided into commendable interpretations that adhere to the principles of Quranic exegesis and blameworthy interpretations that often deviate from Islamic law. Meanwhile, tafsir Isyari offers a symbolic and esoteric approach, requiring strict conditions to ensure relevance and alignment with the apparent meaning of the verses. Although scholars have differing opinions regarding the validity of these interpretative methods, they collectively reflect the intellectual richness of Islam in interpreting the Qur'an to meet the spiritual and intellectual needs of the community across different contexts and eras.